Clinical Presentation of Pancytopenia in children under 15 years of Age - Rehman, Habib ur; Fazil, Muhammad; Muhammad, Faiz (Journal of Postgraduate Medical Institute, 2011)
The aim of the study was to know the clinical presentation and the most common clinical manifestation of pancytopenia in children upto 15 years of age. This was a hospital based propective study carried out in the department of paediatrics, LRH, Peshawar from 1st January 2001 to 31st December 2001. 60 patients who fulfilled the inclusion criteria were included in our study.